Trajectories anonymous algorithm for association attack - Lei ZHANG; Chun-guang MA; Song-tao YANG; Zeng-peng LI (网络与信息安全学报)
During the location based service of continuous query,the trajectories which were produced by different movement types may reveal the privacy of user’s location.To solve this problem,a mechanism was proposed to put forward the real-time similar trajectories.With this mechanism,the subsequent position was calculated and which the dummy one was generated to establish an anonymous group,the demands of real-time trajectory anonymity were met,compensating the shortage of real-time trajectories of anonymity in other similar kinds of algorithm.Under this mechanism,a method for calculating subsequent anonymous position was proposed,which used the user's movement patterns,such as mobile direction,speed.The dummy trajectories were made very similar with the trajectory produced by the continuous query user.At the same time,the position of reachable difference in real areas was put forward,and on the basis of position reachable,this mechanism also filtrates out the unreachable candidate locations which had been calculated in the phase of dummy position generates,then decrease the probability of adversary identifies the real trajectory from the location of unreachable.Experimental results show that this method is effective for protecting the location privacy of continuous query user,and provides a good working efficiency.